Optimizing School Financial Management through the School Financial Management Information System (SIMKEU-EDU) - Herry Sanoto; Dani Kusuma; Nobitha Triwijayanti (Universitas Negeri Padang, 2026)
This study aims to analyze and optimize school financial management through the implementation of the School Financial Management Information System (SIMKEU-EDU) as a solution to inefficiencies in manual financial administration at SDK Manahan Surakarta. The research employs a mixed-method approach combining qualitative and quantitative analyses. Qualitative data were obtained through observation, interviews, and document analysis using triangulation, while quantitative data were used to measure the validity, effectiveness, and practicality of the system. The qualitative findings reveal that manual financial recording is prone to human error, data duplication, and delays in reporting, making financial monitoring and accountability difficult. In contrast, the SIMKEU-EDU system enables digital recording, automatic transaction tracking, and real-time financial reporting, significantly reducing administrative errors and time inefficiencies. Quantitative analysis demonstrates high system validity with an average score of 92.4%, high effectiveness shown by a 45% reduction in transaction processing time and a 60% increase in reporting accuracy, and strong practicality indicated by 90% user satisfaction among school administrators. The study concludes that SIMKEU-EDU is valid, effective, and practical for optimizing financial management, supporting digital transformation, and improving governance in school administration.